Humanitarian Aid for Flash Flood Victims in Batu Busuak: An International Collaboration between STAI As-Sunnah and Bayaan Association Singapore - Slamet Riyadi; Lubis, Arbonas; Fian Triadi; Hasugian, Dirja; Zulham Effendi; Hasibuan, Muhammad Syarif Muda; Khairul Anhar; Syahri Ramadona; Muhajirah binti Jamaluddin (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
The flash flood disaster that struck Batu Busuak, Padang City, in November-December 2025 caused massive damage to residential areas. Within three weeks, this area experienced four consecutive flash floods that swept away 11 houses, severely damaged 46 houses, and forced hundreds of families to evacuate. This community service activity aimed to provide humanitarian aid in the form of necessities to flood victims through international collaboration between Sekolah Tinggi Agama Islam (STAI) As-Sunnah Deli Serdang and Bayaan Association Singapore. The service partners were flood-affected communities in Koto Panjang Ikua Koto Sub-district, Koto Tangah District, and Batu Busuak, Lambung Bukik Sub-district, Pauh District, Padang City. Implementation methods included multi-institutional coordination, international fundraising, local procurement of aid, and door-to-door and distribution-point delivery. A total of IDR 57,000,000 was collected and used to procure necessity packages for 150 affected households. The activity was conducted on December 24-27, 2025, and was led directly by the Chairman of STAI As-Sunnah. The results showed that aid distribution successfully reached victims in isolated locations using adaptive methods according to field conditions. Community response was very positive despite high psychosocial trauma, where residents lived in constant vigilance against subsequent flood threats. This activity was also followed by sustainability programs, including plans to build mosques and bore wells, undertaken by Yayasan Peduli Kemanusiaan Arrisalah as long-term recovery efforts. The Singapore-Indonesia international collaboration in this activity demonstrated the effectiveness of global Islamic philanthropy networks for local emergency response.